2004
DOI: 10.1002/app.21018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of epoxy resins prepared under microwave irradiation

Abstract: ABSTRACT:A new microwave-assisted method of synthesis of solid epoxy resins (SER) with desired epoxy-groups content is described. The method is based on the polyaddition of 4,4Ј-isopropylidenediphenol (BPA) to a lower-molecular-weight epoxy resin [Rü tapox 0162, epoxy value (EV) ϭ 0.57 mol/100 g] in the presence of 2-methylimidazole (2-MI), as a catalyst. Analogical syntheses were performed using conventional heating (i.e., electric heating mantle) for the comparison of properties of SER under both conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The peaks in Figure 4(a) at wavenumber 1,108 cm −1 were attributed to the presence of stretching vibration of polyoxyethylene units which also appeared in (b) and (c), indicating that M1000 had already reacted with the epoxy resin. The peak at wavenumber 916 cm −1 in the spectrum (b) shown the vibration of the rest epoxy groups(Bogdal and Gorczyk, 2004, Kishi et al , 2011), which disappeared in the spectrum (c). Hence, it can be concluded that both of M1000 and TETA had been successfully drafted to the epoxy resin.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks in Figure 4(a) at wavenumber 1,108 cm −1 were attributed to the presence of stretching vibration of polyoxyethylene units which also appeared in (b) and (c), indicating that M1000 had already reacted with the epoxy resin. The peak at wavenumber 916 cm −1 in the spectrum (b) shown the vibration of the rest epoxy groups(Bogdal and Gorczyk, 2004, Kishi et al , 2011), which disappeared in the spectrum (c). Hence, it can be concluded that both of M1000 and TETA had been successfully drafted to the epoxy resin.…”
Section: Resultsmentioning
confidence: 99%
“…Alternate curing methods have been tried and tested for quite some time now. They are: UV rays, Gamma rays, Electron Beam and Microwave (Bogdal et al, 2003;Clark & Sutton, 1996). Curing using UV light has limited application because of its poor penetrability and limited dose rate; it cannot cure thick materials (Wiesbrock et al, 2004).…”
Section: The Dispersion Synthesis and Curing Of Epoxy-based Nanocommentioning
confidence: 99%
“…Since the first report of microwave-assisted synthesis in 1986, the technique has been accepted as a method for reducing reaction times and for increasing yields of products compared to conventional heating methods (Gedye et al 1986). Microwave, supplies a clean and inexpensive alternative to conventional oil baths (Bogdal and Gorczyk 2004;Melo-Junior et al 2009;Wiesbroc et al 2005). Microwave irradiation, in polymer chemistry, is used for developing different types of polymerizations including addition polymerization, condensation polymerization, and so on (Hoogenboom and Schubert 2007;Mallakpour and Zadehnazari 2010).…”
Section: Introductionmentioning
confidence: 99%